" ACTUS REUS‎ in the Crime of Guardian Negligence in Caring for a Minor or Juvenile" - Sabah Abdali, Researcher. Sarah; Hamad Alhamad , Prof. Dr. Hasan (Basra studies journal, 2023)
"Often, we witness many minors and juveniles deviating or becoming homeless, and we wonder about the reasons that lead them down this path. One of the reasons that may drive them is the neglect of their guardians in providing proper care that protects them from harm. The Iraqi Law for the Care of Juveniles, effective Law No. 86 of 1979, in Article 29 states: Firstly, any guardian who neglects the care of a minor or juvenile, leading to their homelessness or deviant behavior, shall be punished with a fine of no less than one hundred dinars and not exceeding five hundred dinars. Secondly, the penalty shall be a fine of no less than two hundred dinars and not exceeding one thousand dinars if this neglect results in the juvenile committing a misdemeanor or intentional crime. To establish this crime, both its material and moral elements must be present. In our discussion, the material element is realized when the guardian exhibits behavior that falls short of their duty in caring for the minor or juvenile, leading to their homelessness or deviation. There must be a causal connection between the neglect and the result, as stipulated by Iraqi penal law concerning the causation theories."